Influência da ativação ultrassônica do ácido glicólico na resistência de união de pinos de fibra de vidro cimentados com cimento resinoso auto-adesivo à dentina radicular – estudo in vitro - Santos, Eduardo Winck dos (2022)
This study aims to evaluate, in vitro, the influence of ultrasonic activation of glycolic acid on the bond strength of restorative material to root dentin. Thirty extracted single-rooted human teeth were used in the present study. The coronal portion was sectioned, having a radicular remainder that presents a length of 15 mm. Then, the working length of the canal was stipulated and enlarged using the ProTaper Next rotary system (Dentsply Maillefer, Ballaigues, Switzerland), following the sequence of X1, X2 and X3 files. After instrumentation, the 30 samples were randomly divided into 3 groups (n=10), according to the final washing protocols to remove the smear layer: G1 – distilled water (control), G2 – Glycolic acid 17%, G3 – 17% glycolic acid + ultrasonic activation. The final irrigant remained in the canal for a period of 1 minute. Next, the fiberglass post was cemented inside the root canal with self-adhesive cement and the roots were stored for 21 days. After this period, horizontal sections were performed on the roots, obtaining 5 discs of 1 mm thickness from each root, totaling 50 discs per group (n=5x10=50). These disks were submitted to the push-out test using a universal testing machine and observed under an optical microscope. The samples were classified according to the type of failure: adhesive, cohesive and mixed. Specific statistical analysis was performed to evaluate the data obtained, with a significance level of 5%. The results showed that the highest bond strength values were observed in groups 2 (GA) and 3 (GA+US), with no statistically significant difference between them (p>0.05). It was possible to conclude that the ultrasonic activation of glycolic acid did not influence the bond strength of restorative material to root dentin.